The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1017/prp.2012.9
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on ‘Cultural Diversity Across the Pacific’: Samoan Cultural Constructs of Emotion, New Zealand-Born Samoan Youth Suicidal Behaviours, and Culturally Competent Human Services

Abstract: A recent special section on cultural diversity across the Pacific, in this journal, highlighted the need for greater alignment between human services and cultural diversity in the region. Alignment entails detailing a local context. Samoan cultural constructs of emotion, particularly anger and shame, may precede suicidal behaviours among New Zealand-born (NZ-born) Samoan youth. These behaviours can stem from perceived ruptures in family unity, as youth partly identify with majority norms. A barrier to integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Pacific perceptions of emotions and mental wellbeing offer alternative worldviews than those that dominate the mainstream literature. Without making sweeping generalisations, Western views of mental wellbeing are often biomedically framed and individualistic [37,48,49,50,51]. Pulotu-Endemann, Annandale, and Instone [50] argued that Western perceptions of mental wellbeing tend to derive from clinical perspectives that must be objective in their explanations of mental wellbeing and illness in order to facilitate standardised medical diagnoses.…”
Section: Sociocultural Contextmentioning
confidence: 99%
“…Pacific perceptions of emotions and mental wellbeing offer alternative worldviews than those that dominate the mainstream literature. Without making sweeping generalisations, Western views of mental wellbeing are often biomedically framed and individualistic [37,48,49,50,51]. Pulotu-Endemann, Annandale, and Instone [50] argued that Western perceptions of mental wellbeing tend to derive from clinical perspectives that must be objective in their explanations of mental wellbeing and illness in order to facilitate standardised medical diagnoses.…”
Section: Sociocultural Contextmentioning
confidence: 99%
“…Pacific perceptions of mental health, both traditional and contemporary, differ to those found in mainstream literature. Without making any conclusive generalisations, Western views of mental health are often based on clinical and biomedical paradigms and tend to take an individualised stance (Alefaio 2009;Bush et al 2009;Pulotu-Endemann et al 2004;Tiatia 2012;Tukuitonga 2013). Fuimaono Pulotu-Endemann et al (2004) argued that this is the case because Western perceptions of mental health tend to be derived from clinical perspectives that must be objective in their explanations of mental health so that medical diagnoses can be standardised.…”
Section: Pacific Mental Wellbeing In New Zealand Pacific Perceptions mentioning
confidence: 99%
“…Challenges for this second generation may include identity tensions. Typically, a Samoan identity is a relational identity based on collectivist ideals (Tamasese, Peteru, Waldegrave, & Bush, 2005;Tiatia, 2012) where individuals have a strong sense of responsibility to their social groups. In contrast, the dominant Australian identity is underpinned by the ideal of individualism (Noordin & Jusoff, 2010).…”
mentioning
confidence: 99%
“…The research literature suggests this common aspect of their identity is tempered by tensions afforded by moving in two non-aligned worlds associated with home and school (Benham, 2006;Kearney, Fletcher, & Dobrenov-Major, 2011). While research in an Australian context remains limited, studies in New Zealand have shown that the second generation have been caught between cultures; and pulled between obligations to their Island heritage and participation in Western society (Anae, Anderson, Benseman, & Coxon, 2002;Manuela & Sibley, 2015;Tiatia, 2012). Tiatia (1998Tiatia ( , 2012 explained that Samoan elders may regard their young peoples' westernised thinking as a threat to cultural traditions, while schools may disregard and discount Samoan students' cultural knowledge.…”
mentioning
confidence: 99%
See 1 more Smart Citation